2023
DOI: 10.1021/acs.est.2c07694
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Bromine Radical with Dissolved Organic Matter Moieties and Monochloramine: Effect on Bromate Formation during Ozonation

Abstract: Bromine radical (Br•) has been hypothesized to be a key intermediate of bromate formation during ozonation. Once formed, Br• further reacts with ozone to eventually form bromate. However, this reaction competes with the reaction of Br• with dissolved organic matter (DOM), of which reactivity and reaction mechanisms are less studied to date. To fill this gap, this study determined the second-order rate constant (k) of the reactions of selected organic model compounds, a DOM isolate, and monochloramine (NH2Cl) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…The Br • /Br 2 •– concentration ratio is ∼1 at 500 μg/L bromide. Therefore, for low to moderate bromide levels, Br • will always dominate and therefore contribute to further reactions with ozone. Another important sink for Br • is DOM, with second-order rate constants ( k ) in the range of 1.4–4.2 × 10 8 M C –1 s –1 for DOM isolates and real waters. , Experiments with a preozonated DOM isolate showed that the second-order rate constant with Br • did not change significantly, which implies a constant consumption of Br • by DOM during ozonation …”
Section: Bromate Formation During Ozonationmentioning
confidence: 99%
See 4 more Smart Citations
“…The Br • /Br 2 •– concentration ratio is ∼1 at 500 μg/L bromide. Therefore, for low to moderate bromide levels, Br • will always dominate and therefore contribute to further reactions with ozone. Another important sink for Br • is DOM, with second-order rate constants ( k ) in the range of 1.4–4.2 × 10 8 M C –1 s –1 for DOM isolates and real waters. , Experiments with a preozonated DOM isolate showed that the second-order rate constant with Br • did not change significantly, which implies a constant consumption of Br • by DOM during ozonation …”
Section: Bromate Formation During Ozonationmentioning
confidence: 99%
“…Reactions of Br • with organic compounds proceed mainly by electron transfer, shown for DOM in eq : normalB normalr + normalD normalO normalM normalB normalr + normalD normalO normalM •+ It has been demonstrated that a minor fraction may proceed by an addition of bromine to the ensuing brominated products …”
Section: Bromate Formation During Ozonationmentioning
confidence: 99%
See 3 more Smart Citations